Behaviors of floating droplet - Kan, Kah Hou (Nanyang Technological University, 2022)
The evaporation of droplets is ubiquitous in nature and has found its way in many industrial applications and everyday processes. While most research on droplet are constraint to single component sessile droplet, the complex mechanism in multicomponent droplet has shown diverse behaviours as the different component concentration yields different evaporation profile and surface tension. Additionally, interesting flow pattern can form in a floating droplet partially submersed in an immiscible liquid by the preferential evaporation in an asymmetric evaporation field. In this report, the underlying physicochemical mechanism and interactions between a binary droplet and its surrounding oil pool are experimentally investigated. Particularly, this research focus on a binary droplet system composed of Isopropyl alcohol and water. It overviews the droplet contact line dynamics and the intrinsic flow pattern during the evaporation of the binary droplet floating on a silicone oil pool. Investigation reveals the formation and transition of flow pattern and vorticity originates from the complex thermo-solutal Marangoni convection induced by the evaporating cap. A droplet forming two stable axis-symmetrical counter circulating flow during evaporation is seen to collapse into a large rotating vortical flow non-periodically. Further analysis on the droplet contact line reveals an oscillating behaviour which follows a spatiotemporal variation in amplitude and frequencies. High amplitude oscillation is characterized by a gradual contraction of contact line and followed by a steep and sharp expansion. Closer inspection shows that the expansion of droplet contact line causes the strong expulsion of bulk fluid into the submersed section causing abrupt and unstable flow transition. The effect of contact diameter size on the relative amplitude and frequency of oscillation, and hence the strength and flow structures were explored, and data from surrounding fluid viscosity and temperature, as well as droplet size and concentration are reported to affect the equilibrium size of the contact diameter. The measured contact diameter and oscillation was found to have a negative correlation between the oscillation, i.e., smaller contact diameter resulting in more frequent contraction and expansion behaviours. Lastly, an aspect ratio studies of the relative size of droplet contact diameter quantitatively captures the interactive forces between the droplet and surrounding oil and predicts the essential features of the oscillating motion.